In Vitro Cultivars of Vaccinium corymbosum L. (Ericaceae) are a Source of Antioxidant Phenolics - Rodrigo A. Contreras; Hans Köhler; Marisol Pizarro; Gustavo E. Zúiga (MDPI AG, 2015)
The antioxidant activity and phenolic composition of six in vitro cultured blueberry seedlings were determined. Extracts were prepared in 85% ethanol from 30 days old in vitro cultured plants and used to evaluate the antioxidant capacities that included Ferric reducing antioxidant power (FRAP) and 1,1-diphenyl-2-picrylhydrazin (DPPH•) scavenging ability, total polyphenols (TP) and the partial phenolic composition performed by high performance liquid chromatography with diode array detector (HPLC-DAD), liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS (ESI-QqQ)). All ethanolic extracts from in vitro blueberry cultivars displayed antioxidant activity, with Legacy, Elliott and Bluegold cultivars being the most active. In addition, we observed a positive correlation between phenolic content and antioxidant activity. Our results suggest that the antioxidant activity of the extracts is related to the content of chlorogenic acid myricetin, syringic acid and rutin, and tissue culture of blueberry seedlings is a good tool to obtain antioxidant extracts with reproducible profile of compounds.